Surface ferromagnetism of lead-free ferroelectric bismuth sodium titanate materials - Dung, Dang Duc; Vu, Tien Lam; Nguyen, Huu Lam; Duong, Quoc Van; Nguyen, Hoang Thoan; Nguyen, Hoang Linh; Nguyen, Ngoc Trung (Communications in Physics, 2024)
The role of complex surface defect on the magnetic at the (110) surface of bismuth sodium titanate (Bi0.5Na0.5TiO3) was discussed based on the first-principles calculation. The first-principle calculations for various types of surface defects exhibited the existence of magnetic moments for selected chemical and position defects. Specifically, Na and Bi vacancies induced large magnetic moments of 0.52 µB/f.u and 0.50 µB/f.u, respectively, which were larger than that of Ti vacancies of 0.01 µB/f.u. Interestingly, oxygen vacancies did not induce local magnetic moments. Furthermore, significant magnetic moments of 0.50 µB/f.u and 0.49 µB/f.u were obtained for Na and Bi interstitial defects, while the local magnetic moments were slightly achieved around 0.03 µB/f.u and 0.04 µB/f.u for Ti and O interstitial defects, respectively. Anti-site defects between Bi and Na at A-site in perovskite ABO3 structure exhibited magnetic moments of 0.55 µB/f.u for Na anti-site at Bi-site and 0.39 µB/f.u for Bi anti-site at Na-site. Interestingly, anti-site defects between the A-site and B-site in perovskite ABO3 structure resulted in larger magnetic moments, with values of 0.57 µB/f.u and 0.53 µB/f.u obtained for Ti anti-site defects at the Bi-site and Na-site, respectively. Additionally, magnetic moments of 0.50 µB/f.u and 0.54 µB/f.u were achieved for Bi and Na anti-site defects at the Ti-site, respectively. We expected that our work further contributed to the understanding of the role of surface defects in the magnetism of Bi0.5Na0.5TiO3 materials in integrating ferromagnetic properties into lead-free ferroelectric materials for smart electronic device applications.